The Effect of Concentration and Fineness of Roasted Corn Flour on the Physicochemical and Sensory Quality of Lollies Ice - Alex Frans GL Tobing; Terip Karo-Karo; Elisa Julianti (Jurnal Rekayasa Pangan dan Pertanian, 2016)
Lollies ice are frozen beverage products with solid phase and belong to one of the water ice products, which tend to taste sweet with economical purchase price. The aim of this research was to know the combination of concentration and fineness of the roasted roasted corn flour in producing lollies ice with th best physicochemical and sensory characteristics that can be accepted by consumers. The research was using completely randomized design with two factors, i.e the concentration of roasted corn flour consisted of 5 levels i.e 2%, 4%, 6%, 8%, and 10% and roasted corn flour fineness consisted of 3 levels i.e 60 mesh, 80 mesh and 100 mesh. The parameters analyzed were physical quality characteristics (color, melting rate), chemical (pH, total soluble solids, ash content (mineral), total solids), and sensory characteristics (color, flavor, taste, and texture). The results showed that the interaction between concentration of roasted corn flour fineness had a highly significant effect (P <0,01) on a score of texture. The increasing concentrations of roasted corn flour decreased the color value (oHue), pH, melting rate and increased the value of total solids and ash content (mineral) of lollies ice. The lollies ice with the best quality was based on the characteristics of sensory by hedonic test with % AI (Acceptable Index) value was the concentration of 6% roasted corn flour and a fineness of 100 mesh. The best lollies ice had total value of sugar of 22.99% which already met the minimum addition of sugar to the quality standard (8.0%) and total microbes of 7.46 x 102 CFU / ml which showed a lower amount than the maximum permissible total microbes standard (1 x 104 CFU / ml). Keywords: Flour roasted corn kernels, finenees of flour, lollies ice